Code-switching in advertising : an exploratory study on "Manglish" and "Bahasa Rojak" in newspaper and advertisements / Noraminah Ibrahim - Ibrahim, Noraminah (2013)
This study seeks to analyse the occurrence of code-switching in Malaysian advettising industry by focussing on "Manglish" and "bahasa roja/f' phenomena. Code-switching occurs when more than one language is used simultaneously, or when different languages are mixed and switched during the same communication process. Advertising as one form of marketing communication and newspaper as an influential medium have been evolving due to various factors, thus code-switching in newspaper advertisements appears to be inevitable. In this study, a content analysis over a period of six months has been piloted on two leading newspapers in the country, namely The Star and Harian Metro. Over three hundred advertisement samples containing over one thousand code-switching incidences are analysed to accomplish the objectives of the study. As Chinese New Year was celebrated amidst the analysis period, words related to the festivity are commonly used in numerous advertisements. Additionally, several other technical jargons and catchy texts that signify promotional campaigns are prevalent too. The language types and locations of the code-switched incidences on the other hand differ according to newspaper, although both newspapers share similar code-switching categories. Consequently, this study also aims to identify the common brand categories and brand origins, as well as target audiences of the advertisements. The importance of language in conveying advertising messages allows this study to be significant to industry practitioners and parties of interest in realising that code-switching occurrence in advertising is an essential prospect of mass communication landscape, particularly in a culturally diversified and fast-developing nation like Malaysia.